Industries, Mega Firms, and Increasing Inequality - John C. Haltiwanger; Henry R. Hyatt; James R. Spletzer (Institute of Labor Economics (IZA), 2022)
Most of the rise in overall earnings inequality is accounted for by rising between-industry dispersion from about ten percent of 4-digit NAICS industries. These thirty industries are in the tails of the earnings distribution, and are clustered especially in high-paying high-tech and low-paying retail sectors. The remaining ninety percent of industries contribute little to between-industry earnings inequality. The rise of employment in mega firms is concentrated in the thirty industries that dominate rising earnings inequality. Among these industries, earnings differentials for the mega firms relative to small firms decline in the low-paying industries but increase in the high-paying industries. We also find that increased sorting and segregation of workers across firms mainly occurs between industries rather than within industries.
Keywords: J31; J21; 330; inequality; firm size; industry; wage differentials; sorting; segregation; pay premium